2001
DOI: 10.2337/diacare.24.1.111
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Sensitivity Related to Albuminuria Appearing Before Hypertension in Type 2 Diabetic Patients

Abstract: Abbreviations: ANOVA, analysis of variance; MAP, mean arterial pressure; SSI, sodium sensitivity index; UNaV, urinary sodium excretion.A table elsewhere in this issue shows conventional and Système International (SI) units and conversion factors for many substances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 27 publications
2
40
0
1
Order By: Relevance
“…In agreement with our previous studies, 9 the present study showed that BP was salt sensitive from an early stage in patients with type 2 diabetic nephropathy who had microalbuminuria. The finding that salt sensitivity of BP was associated with reduced urinary excretion of NOx suggests a possible contribution of reduced intrarenal NO bioactivity to the development of salt-dependent hypertension in patients with diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In agreement with our previous studies, 9 the present study showed that BP was salt sensitive from an early stage in patients with type 2 diabetic nephropathy who had microalbuminuria. The finding that salt sensitivity of BP was associated with reduced urinary excretion of NOx suggests a possible contribution of reduced intrarenal NO bioactivity to the development of salt-dependent hypertension in patients with diabetic nephropathy.…”
Section: Discussionsupporting
confidence: 94%
“…15 Similar results have also been reported in Dahl salt-sensitive hypertensive rats, 16 which show reduced intrarenal NO levels. 5 The present finding that patients with type 2 diabetic nephropathy display reduced urinary excretion of NOx and increased salt sensitivity of BP, combined with results from previous studies, 2,4,7,9,15,16 is consistent with the concept that salt sensitivity of BP is induced by decreased intrarenal NO bioactivity in patients with diabetic nephropathy. We observed that treatment with an ARB restored reduced urinary renal NOx excretion in patients with type 2 diabetic nephropathy and microalbuminuria.…”
Section: Discussionsupporting
confidence: 90%
“…[Diabetologia (2004) 47:300-303] Keywords Microalbuminuria · Salt sensitivity · Type 2 diabetes · Glomerular filtration rate · Renal plasma flow · Intraglomerular pressure · Insulin resistance increased exchangeable sodium pool in diabetic patients [2], few studies have addressed the role of sodium intake on blood pressure and kidney haemodynamics in Type 2 diabetes. Recently it was shown that in Type 1 and in Type 2 diabetic patients with increased albumin excretion the sensitivity of blood pressure to salt intake is greater than in patients with normoalbuminuria [3,4].…”
mentioning
confidence: 99%
“…Blood pressure was measured in the supine position using a sphygmomanometer. Clinical laboratory data were obtained in our institution, as previously reported (13 Nonobstructive disease was defined as a stenosis of 0 -50%. The inter-and intraobserver variability of grading was 8 and 3%, respectively.…”
mentioning
confidence: 99%